Prioritising diplomacy as an instrument of the United States’ foreign policy in the aftermath of the ‘war on terror’ - Spies, Yolanda Kemp (University of Pretoria, 2013)
Mini Dissertation (MDIPS)--University of Pretoria, 2012.